An mHealth Pain Coping Skills Training Intervention for Hematopoietic Stem Cell Transplantation Patients: Development and Pilot Randomized Controlled Trial - Somers, Tamara J; Kelleher, Sarah A; Dorfman, Caroline S; Shelby, Rebecca A; Fisher, Hannah M; Rowe Nichols, Krista; Sullivan, Keith M; Chao, Nelson J; Samsa, Gregory P; Abernethy, Amy P; Keefe, Francis J (JMIR Publications, 2018)
BackgroundPain is a challenge for patients following hematopoietic stem cell transplantation (HCT). ObjectiveThis study aimed to develop and test the feasibility, acceptability, and initial efficacy of a Web-based mobile pain coping skills training (mPCST) protocol designed to address the needs of HCT patients. MethodsParticipants had undergone HCT and reported pain following transplant (N=68). To guide intervention development, qualitative data were collected from focus group participants (n=25) and participants who completed user testing (n=7). After their input was integrated into the mPCST intervention, a pilot randomized controlled trial (RCT, n=36) was conducted to examine the feasibility, acceptability, and initial efficacy of the intervention. Measures of acceptability, pain severity, pain disability, pain self-efficacy, fatigue, and physical disability (self-report and 2-min walk test [2MWT]) were collected. ResultsParticipants in the focus groups and user testing provided qualitative data that were used to iteratively refine the mPCST protocol. Focus group qualitative data included participants' experiences with pain following transplant, perspectives on ways to cope with pain, and suggestions for pain management for other HCT patients. User testing participants provided feedback on the HCT protocol and information on the use of videoconferencing. The final version of the mPCST intervention was designed to bridge the intensive outpatient (1 in-person session) and home settings (5 videoconferencing sessions). A key component of the intervention was a website that provided personalized messages based on daily assessments of pain and activity. The website also provided intervention materials (ie, electronic handouts, short videos, and audio files). The intervention content included pain coping advice from other transplant patients and instructions on how to apply pain coping skills while engaging in meaningful and leisure activities. In the RCT phase of this research, HCT patients (n=36) were randomized to receive the mPCST intervention or to proceed with the treatment as usual. Results revealed that the mPCST participants completed an average of 5 out of 6 sessions. The participants reported that the intervention was highly acceptable (mean 3/4), and they found the sessions to be helpful (mean 8/10) and easy to understand (mean 7/7). The mPCST participants demonstrated significant improvements in pre- to post-treatment pain, self-efficacy (P=.03, d=0.61), and on the 2MWT (P=.03, d=0.66), whereas the patients in the treatment-as-usual group did not report any such improvements. Significant changes in pain disability and fatigue were found in both groups (multiple P<.02); the magnitudes of the effect sizes were larger for the mPCST group than for the control group (pain disability: d=0.79 vs 0.69; fatigue: d=0.94 vs 0.81). There were no significant changes in pain severity in either group. ConclusionsUsing focus groups and user testing, we developed an mPCST protocol that was feasible, acceptable, and beneficial for HCT patients with pain. Trial RegistrationClinicalTrials.gov NCT01984671; https://clinicaltrials.gov/ct2/show/NCT01984671 (Archived by WebCite at http://www.webcitation.org/6xbpx3clZ)